Private actors, NGOs and civil society in multilevel governance - Mende, Janne (Edward Elgar Publishing, 2021)
Multilevel governance is fundamentally marked by the participation of private actors. This has tremendous effects on both private actors and multilevel governance: it transforms and pluralizes the forms of authority in governance. This chapter discusses the resulting reconfiguration of authority in multilevel governance using an authority-based approach that focuses on governance actors' power, legitimacy and connection to public interests. It links the extent of private and public authority to the ways private actors participate in multilevel governance. Furthermore, it outlines the reconfiguration of authority in multilevel governance involving variance in the scope and substance of authority, on different governance levels, and in the effects on multilevel governance. The chapter concludes by suggesting a framework which extends beyond the public-private distinction, enabled by an approach that traces public, private and hybrid roles in multilevel governance authority.